Foliar Litter Decomposition: A Conceptual Model with Focus on Pine (Pinus) Litter—A Genus with Global Distribution. (27th April 2014) - Berg, Björn
Abstract : The genus Pinus encompasses c 120 species and has a global distribution. Today we know more about the decomposition of pine needle litter than litter from any other genus. This paper presents a developed conceptual three-phase model for decomposition, based on pine needle litter, starting with newly shed litter and following the process until a humus-near stable residue. The paper focuses on the mass-loss dynamics and factors regulating the process in the early phase, the late one, and the humus-near phase. For the late phase, the hampering influence of N and the rate-enhancing effect of Mn on the decomposition are given extra attention. Empirical factors related to the limit value/stable residue are discussed as well as the decomposition patterns and functions for calculating limit values. The climate-related litter concentrations of N and Mn are discussed as well as their possible influence on the size of the stable residue, which may accumulate and sequester carbon, for example, in humus layers. The sequestration of carbon in humus layers is discussed as well as the effect of tree species on the process. Although the paper focuses on litter of pine species, there are comparisons to studies on other litter genera and similarities and differences are discussed.